Mindfulness for Singers: A Mixed Methods Replication Study. (15th September 2021) - Czajkowski, Anne-Marie Louise; Greasley, Alinka Elizabeth; Allis, Michael
Objectives: Mindfulness has been explored in the clinical and educational fields but has rarely been studied in the music domain. This study investigated the effects of teaching eight-week Mindfulness for Singers courses on vocalists' music education and performance. Methods: A mixed methods approach was utilized, which included controlled and randomized controlled trials using standardized and novel mindfulness measures pre- and post-intervention, interviews post-intervention and three months later, concurrent diaries, and a blinded teacher study. Participants included singing students (total n =52) and their teachers ( n =11) from a university and a music college over a period of two years. Results: Levels of mindfulness increased over the intervention for experimental participants in comparison to controls. Considering their total student cohort, teachers identified 61% of eligible mindfulness singing participants as having completed the mindfulness intervention. Experimental participants reported that learning mindfulness had positive effects in lessons, solo and group instrumental practices, and when performing on stage. They described more focus and attention, positive effects of increased body awareness on singing technique, enhanced socio-collaborative relationships, reductions in performance anxiety, and beneficial effects whilst performing, such as more expressivity and enjoyment. Conclusions: Learning mindfulness had positive holistic effects on vocal students and was well received by their mindfulness-naïve singing teachers. Findings suggest that it would be highly beneficial for mindfulness to be made available in music conservatoires and university music departments alongside singing lessons for singers to enhance their present experience as vocal students and their futures as performers and teachers.